To determine whether the values \( x = 10 \) and \( x = 30 \) are solutions to the equation
\[ (x - 27)(x - 10) = 60, \]
we can plug in each value into the equation and see if the equation holds true.
Testing \( x = 10 \):
Substituting \( x = 10 \):
\[ (10 - 27)(10 - 10) = 60. \]
This simplifies to:
\[ (-17)(0) = 60. \]
Since \( 0 \neq 60 \), \( x = 10 \) is not a solution.
Testing \( x = 30 \):
Now, substituting \( x = 30 \):
\[ (30 - 27)(30 - 10) = 60. \]
This simplifies to:
\[ (3)(20) = 60. \]
Since \( 60 = 60 \), \( x = 30 \) is a solution.
Conclusion:
Thus, the correct response is:
Only \( x = 30 \) is a solution.